Status Psikososial Remaja Usia 15-17 Tahun yang Mengalami Maloklusi Anterior Berdasarkan Indeks PIDAQ - Tilaar, Keren D.; Anindita, Pritartha S.; Pangemanan, Damajanty H. C. (e-GiGi, 2026)
Abstract: Anterior malocclusion can affect facial aesthetics and has an impact on psychosocial condition, particularly among adolescents. Coastal areas like Tuminting District, which is close to the center of Manado City, have social characteristics that make appearance an important aspect of adolescent interactions, while socio-economic conditions often limit access to orthodontic care, which further influences the psychosocial impact of malocclusion. This study aimed to obtain the psychosocial status of adolescents aged 15-17 tahun with anterior malocclusion based on PIDAC at SMAN3 Tuminting. This was a descriptive and observational study with a cross-sectional approach. Respondents consisted of 60 students aged 15–17 years selected through purposive sampling based on inclusion and exclusion criteria. Visual monitoring was conducted to detect anterior malocclusion, and the PIDAQ questionnaire was administered to assess psychosocial impact. The majority of study subjects (61.6%) fell into the moderate PIDAQ score category, 21.7% into the high category, and 16.7% into the low category. Female subjects tended to have higher PIDAQ scores than males, reflecting greater sensitivity to dental aesthetics. In conclusion, most adolescents with anterior malocclusion at SMAN 3 Tuminting fall into the moderate PIDAQ score category indicating that anterior malocclusion has a psychosocial impact. Keywords: anterior malocclusion; adolescents; psychosocial status; PIDAQ   Abstrak: Maloklusi anterior dapat memengaruhi estetika wajah dan berdampak pada kondisi psikososial, terutama pada remaja. Daerah pesisir seperti Kecamatan Tuminting yang tidak jauh dari pusat Kota Manado memiliki karakteristik sosial yang menjadikan penampilan sebagai aspek penting dalam interaksi remaja, sementara kondisi sosio-ekonomi sering membatasi akses terhadap perawatan ortodontik, yang turut memengaruhi dampak psikososial akibat maloklusi. Penelitian ini bertujuan mengetahui status psikososial remaja usia 15–17 tahun dengan maloklusi anterior berdasarkan indeks PIDAQ di SMAN 3 Tuminting. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Responden penelitian berjumlah 60 siswa berusia 15–17 tahun yang telah dipilih melalui purposive sampling sesuai kriteria inklusi dan eksklusi. Pemantauan visual dilakukan untuk mendeteksi maloklusi anterior dan pengisian kuesioner PIDAQ untuk menilai dampak psikososial. Mayoritas responden sebanyak 61,6% tergolong skor PIDAQ kategori sedang, 21,7% kategori tinggi, dan 16,7% kategori rendah. Responden perempuan cenderung memiliki skor PIDAQ lebih tinggi daripada laki-laki, yang mencerminkan sensitivitas lebih besar terhadap estetika gigi. Simpulan penelitian ini ialah sebagian besar remaja dengan maloklusi anterior di SMAN 3 Tuminting tergolong dalam kategori skor PIDAQ sedang, yang menunjukkan bahwa maloklusi anterior memberikan dampak psikososial. Kata kunci: maloklusi anterior; remaja; status psikososial; PIDAQ